2017
DOI: 10.1098/rsif.2016.0993
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of dependencies between growth and division in budding yeast

Abstract: Cell growth and division are processes vital to the proliferation and development of life. Coordination between these two processes has been recognized for decades in a variety of organisms. In the budding yeast Saccharomyces cerevisiae, this coordination or 'size control' appears as an inverse correlation between cell size and the rate of cell-cycle progression, routinely observed in G 1 prior to cell division commitment. Beyond this point, cells are presumed to complete S/G 2 /M at similar rates and in a siz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 44 publications
4
21
0
Order By: Relevance
“…This phenomenon explains the previously reported ( Cookson et al, 2005 ) progressive shortening of the cell cycle duration with the replicative age of the cell (see also Figure 1—figure supplement 9 ). Also, our result recapitulate the systematic shorter S/G2/M interval in mother cells compared to daughters that was recently measured( Mayhew et al, 2017 ). Over, these findings illustrate the power of our technique to quantitatively measure the temporal distribution of cell cycle intervals.…”
Section: Resultssupporting
confidence: 91%
“…This phenomenon explains the previously reported ( Cookson et al, 2005 ) progressive shortening of the cell cycle duration with the replicative age of the cell (see also Figure 1—figure supplement 9 ). Also, our result recapitulate the systematic shorter S/G2/M interval in mother cells compared to daughters that was recently measured( Mayhew et al, 2017 ). Over, these findings illustrate the power of our technique to quantitatively measure the temporal distribution of cell cycle intervals.…”
Section: Resultssupporting
confidence: 91%
“…Figure 1, B and D), in agreement with observations from other groups(Anastasia et al 2012;Ferrezuelo et al 2012;Dowling et al 2014;Soifer and Barkai 2014;Cerulus et al 2016;Mayhew et al 2017;Garmendia-Torres et al 2018).…”
supporting
confidence: 91%
“…Adder correlations in diploid budding yeast cells are robust across a range of growth media, and show that passage through Start cannot follow the previously favored “size threshold” policy; a threshold in volume at Start would cause any correlation between cell size at birth and division to vanish. These correlations also highlight a potential difference in size regulation between haploid and diploid cells, since it has been noted recently that adder behavior is not observed in haploid daughter cells (Mayhew et al, 2017 ). Despite this, adder size correlations in diploid cells may be consistent with the molecular mechanism outlined above: in the idealized noiseless case it has been shown that a dilution model compatible with the Whi5 dilution hypothesis can reproduce these adder correlations between volume at birth and at division (Soifer et al, 2016 ).…”
Section: Introductionmentioning
confidence: 59%
“…This assumption stands in apparent opposition to observations in haploids that the concentration of Whi5 in the bud nucleus is higher than in the main cell nucleus at cell division (Liu et al, 2015 ; Schmoller et al, 2015 ). Further work should investigate this discrepancy by studying the distribution of Whi5 between mother and daughter at cell division in diploid cells, since these are the relevant cell type to study adder behavior (Soifer et al, 2016 ; Mayhew et al, 2017 ). Recent work has also demonstrated that adder-like behavior may be generated in a Whi5 dilution model by assuming dynamical changes in Cln3 concentration during G1, in addition to a constant abundance of Whi5 at birth (Delarue et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%